The study of new double perovskites K2AgAsX6 (X = Cl, Br) for energy-based applications - Malak Azmat Ali; Razan A. Alshgari; Aboud Ahmed Awadh Bahajjaj; Mika Sillanpää (Journal of Taibah University for Science, 2023)
Halide double perovskites are the best alternative to Pb-halide perovskites. These materials play an important role in renewable energy generation. Therefore, we explore the physical properties of K2AgAsX6 (X = Cl, Br) double halide perovskites using full potential linearized augmented plane wave method . The structural parameters are calculated by optimization and analytical schemes. The negative values of formation energy confirm the thermodynamic stability, while Goldsmith’s tolerance factor guarantees the structural stability of both the double perovskites. The bandgaps of K2AgAsCl6 and K2AgAsBr6 are calculated as 2.10 and 1.48 eV, respectively by modified Becke and Johnson potential. Optical properties are examined in terms of the dielectric function, refractive index and absorption coefficients. The thermoelectric properties are calculated in terms of the electronic and thermal conductivities, Seebeck coefficients, power factor and figure of merit. Our study suggests the K2AgAsX6 perovskites for energy-related applications.